Atrial Fibrillation Revealing Chronic Constrictive Pericarditis - Bennoui, Zakia; Abdelbaki, Mourad (International Journal of Innovative Research in Medical Science, 2024)
Chronic constrictive pericarditis (CCP) is rare, has multiple cause and is diagnosed late due to the absence of specific signs. It often leads to confusion with restrictive cardiomyopathy. The diagnosis can be oriented by a simple chest x-ray which shows pericardial calcifications in the form of a shell enveloping the cardiac silhouette, and confirmed by cardiac Doppler echo, right heart catheterization, and in some cases cardiac computed tomography (CT) and MRI. We report the case of a 27-year-old female patient hospitalized for suspected restrictive cardiomyopathy with atrial fibrillation, which had been developing for several years. The diagnosis of CCP was made in her. Through this case, we will discuss the diagnostic means and management of this pathology.